CIS Ferro Alloys Industry: Commercial Opportunities, Technical Challenges And Strategic Implications - K. Ford; D. Hobbs; R. Urquhart (The Southern African Institute of Mining and Metallurgy, 2007)
CIS countries are home to some of the world's largest producers of chrome, manganese and silicon ferro alloys and leading suppliers to world export markets. The region's ferro alloys production is rising faster than demand from its domestic steel industry - unit alloy consumption in domestic steelmaking is in fact falling as process efficiencies improve - and there is significant spare capacity available to increase production. CIS producers enjoy certain strategic advantages in the production of ferro alloys - for example, captive ore sup-plies, low power and labour costs - but must also meet certain challenges - such as lower labour productivity and greater distance to market than some of their competitors. CIS producers are ambitious but new investment is needed to upgrade some aging plants and overhaul outdated process technologies if they are to be more competitive with the world's leading producers and address the environmental issues that are now moving up the agenda. This paper describes the structure of the region's ferro alloys industry and discusses its advantages and disadvantages by alloy and by country. It considers how the ongoing process of restructuring and new investment in the industry might move forwards, based on its strengths and weaknesses, technical and environmental factors and the strategies of the main players. It asks how the industry might maximise its substantial potential - in particular, for the production of chrome and manganese ferro alloys - and examines the implications this holds for all global ferro alloys players.